PENELITIAN STATUS HADITH TENTANG MAYAT DISIKSA AKIBAT TANGISAN KELUARGANYA (Analisis Kualitas dan Kuantitas Sanad Hadith) - Abu Azam Al Hadi (Al Hikmah: Jurnal Studi Keislaman, 2014)
The traditions of the Prophet hadist) is the source of Islamic teachingsbesides the Quran. However, both have differences in terms of narration from theProphet. The verses of the Qur'an as a whole are narrated in mutawatir narrations.It is defrerent from hadits. Some of its narrations are mutawatir and some othersare ahad. Therefore based on its status, the Qur'an has the so-called qath'i al-wurudas a whose and is no longer in need of any research on its originality. While interms of hadist, some have zanni al-wurud (especially categorized in the ahadhadists) so to determine whether the hadist has its originality from the Prophet ornot, it is necessary to study hadist in terms the quality and quantity of the chainsof narration (sanad). A study about the hadist on the deceased person tortured dueto the cries of his family, indicates that the hadist narrated by al-Bukhari,Muslim, al-Nasa'i, al-Tirmidhi, Ibn Majah, Malik and Ahmad ibn Hanbal based onthe chains of narrators, has such qualities as thiqah, ma'mun, hujjah, saduq, hafizzli al-Hadith, and ahl 'ilm. The totality of the value of the narrators has the statusmu'asarah and liqa' and can be used as evidence that al-Tirmidhi sanad iscontinued from mukharrij to Prophet Muhammad. While in terms of the quantityof its sanad, the hadist is ahad. This is because the number of the narrators in eachtabaqah is more than two people, two people in the tabaqah of Prophet'scompanions, then continued by the number of many narrators in any tabaqah untilthe so-called mukharrij hadist.